Investigating teachers' perspectives towards using Neuro-linguistic programming in teaching English as a foreign language in Sudan university of Science and Technology and Nile valley university - Adam, Osman Abdelrhman Ishag (The Ahfad journal, 2022)
This study aimed at investigating teachers' perspectives towards using Neuro-linguistic programming in teaching English as a foreign language. The study followed the descriptive analytical method. Questionnaire has been used as tool for data collection. The questionnaire was distributed to (103) university teachers of English language and majors at Sudan university of science and technology and Nile Valley university. The researcher applied (SPSS) program for analyzing and verifying the hypothesis. The results revealed that there are statistical significant differences among the respondents. Using neuro-linguistic programming develops and enhances teaching English as a foreign language. In the light of these results, the study recommended that using Neuro-linguistic programming reinforces English language teaching and creates mutual understanding in the classroom.